2022
DOI: 10.1097/pec.0000000000002580
|View full text |Cite
|
Sign up to set email alerts
|

Pain Prevalence Among Children Visiting Pediatric Emergency Departments

Abstract: Objectives:The main purpose of this study was to investigate the prevalence, characteristics, and intensity of children's pain in emergency departments. The secondary purpose was to evaluate the interobserver agreement regarding the level of pain perceived by professionals, parents, and children.Methods: This was a multicenter, survey-based research study on 0-to 18-year-old patients visiting 1 of the 15 hospitals that form part of the Working Group on Analgesia and Sedation of the Spanish Society of Pediatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…Watching cartoons with a tablet is an effective distraction method, and can reduce pain and fear by concentrating the child's attention on a stimulus other than pain, with both visual and auditory stimuli 7,8. Our findings are consistent with previous studies that showed children, with ages ranging from 3 to 12 years, who watched cartoons during blood draw procedures experienced less pain and fear 7,8,11,41,42. Similarly, Sönmez Düzkaya et al29 found that watching cartoons with a tablet during blood draws was efficient in decreasing the level of pain and anxiety in children 29.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Watching cartoons with a tablet is an effective distraction method, and can reduce pain and fear by concentrating the child's attention on a stimulus other than pain, with both visual and auditory stimuli 7,8. Our findings are consistent with previous studies that showed children, with ages ranging from 3 to 12 years, who watched cartoons during blood draw procedures experienced less pain and fear 7,8,11,41,42. Similarly, Sönmez Düzkaya et al29 found that watching cartoons with a tablet during blood draws was efficient in decreasing the level of pain and anxiety in children 29.…”
Section: Discussionsupporting
confidence: 89%
“…7,8 Our findings are consistent with previous studies that showed children, with ages ranging from 3 to 12 years, who watched cartoons during blood draw procedures experienced less pain and fear. 7,8,11,41,42 Similarly, Sönmez Düzkaya et al 29 found that watching cartoons with a tablet during blood draws was efficient in decreasing the level of pain and anxiety in children. 29 Similar to the results of this study, literature shows that watching cartoons with a tablet during invasive intravascular procedures efficiently decreases pain, fear, and anxiety in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter study developed in Spain describes a prevalence of 53.1% of the patients attended, being severe in 37.1%. 9 Inadequate pain management not only implies anxiety and discomfort in the patient, but also reduces patient collaboration, which can affect the care process. The evaluation of pain in the PED should therefore be systematic and use an appropriate methodology that allows the selection of the ideal drug to achieve maximum effectiveness in pain relief.…”
Section: Pain Management Recommendationsmentioning
confidence: 99%
“…Notably, the effects of local anesthetics and nonpharmacological methods have been tested. Methods include distraction intervention [12][13][14][15][16][17], combined cognitive-behavioral therapy [18,19], hypnosis [20,21], preparation or information [22,23], breathing [24,25], and suggestions that a placebo cream might help the needle to hurt less [26]. Pain and distress are the primary outcomes when evaluating these nonpharmacological interventions, and their effectiveness is determined by reducing these two unpleasant feelings.…”
Section: Introductionmentioning
confidence: 99%